Enforcing Energy Balance in Coherently Superimposed Optical Vortices - Jaime Cisternas; Jaime A. Anguita; Gustavo Funes (IEEE Photonics Journal, 2018)
The generation of optical beams with multiple, mutually coherent orbital-angular-momentum (OAM) modes using phase gratings is analyzed from the perspective of energy distribution and radial mode composition. We show that phase gratings designed with equally weighted Laguerre-Gauss (LG) modes will generate beams with uneven energy distribution among OAM components. This unwanted outcome cannot be corrected by adjusting the width of the illuminating beam. We propose a way to design phase gratings that will produce a uniform energy distribution among the constituent OAM states after illumination while minimizing the content of high radial modes. This method is based on a generalized definition for the LG modes that take advantage of the freedom to select their radial scales.